MASALAH-MASALAH PESERTA DIDIK PINDAH SEKOLAH KE SMA ADABIAH PADANG - Sefriani, Sefriani; Kasih, Fitria; Yusnetti, Yusnetti (Bimbingan dan Konseling, 2013)
The problem in this study is what are the problems of the students moved to high school Adabiah Padang. The purpose of this study was: (1) to determine the learning problems of students move into high school Adabiah Padang (2) to determine the social problems of students move into high school Adabiah Padang (3) to determine the personal problems of students move into high school Adabiah Padang. This research is a descriptive study sought to describe a situation for what it is. The population in this study was the students who move into high school Adabiah Padang totaling 25 peoples. Sampling this study uses total sampling is sampling the researcher if the researcher has used certain considerations in sample collection. So the total sample of 25 peoples. The instrument used in this study was a questionnaire. While the percentage of data analysis techniques used. The research results revealed that: 1) the problem of learners moving into high school Adabiah Padang on the demands of the subject matter is in the category with a slight percentage of 55%, is in preparation for many categories with a percentage of 85%, the motivation to learn is in a lot of categories with percentages 80%, (2) social issues students move into high school Adabiah Padang on the school environment is in many categories with a percentage of 85%, with the social problems of teachers are in many categories with a percentage of 95%, the social problems with peers that are in many categories with a percentage of 80% (3) personal problems of students move into high school Adabiah Padang about emotional problems are in many categories with a percentage of 55%, physical problems are in many categories with a percentage of 90%.